MEKANISME PENYELESAIAN BAGI NASABAH WANPRESTASI - Masturoh, Neneng; Haniatunnisa, Siti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
This study aims to find out how the concept of savings in the form of wadi'ah contract practices in Savings Products at Bank Syariah Mandiri (BSM) Tangerang Balaraja, before the merger of BSM with other Islamic banks. The contract of safekeeping of goods or money between the party who owns the goods or money and the party who is entrusted with the aim of maintaining the safety, security, and integrity of the goods or money is allowed. This is explained by the DSN-MUI Fatwa No. 01-02/DSN-MUI/IV/2002 that savings and demand deposits (without deposits) are allowed using wadiah contracts. The method used in this research is qualitative, with in-depth interview data collection techniques and content analysis. The findings in this study are the practice of wadiah contracts at Bank Syariah Mandiri (BSM) Tangerang Balaraja, fulfilling the provisions of the DSN MUI fatwa and also complying with applicable legal rules. However, the wadiah concept that exists in BSM is still not fully understood by customers, this certainly affects the performance of the BSM.